STRATEGI KOMUNIKASI PEMIMPIN DALAM MEMBANGUN IKLIM ORGANISASI BEMKT UNIVERSITAS ESA UNGGUL TANGERANG - Diana Indriani; Lutfiah Nurhikmah; Nurmala, Nurmala (Cahaya Ilmu Bangsa, 2025)
This research explores the communication strategies of the leader of BEMKT Universitas Esa Unggul Tangerang in creating a conducive organizational climate. Using a qualitative descriptive method, data were collected through questionnaires and interviews. The results show that open and inclusive communication enhances members’ motivation and collaboration. However, challenges such as inconsistent two-way communication and virtual misunderstandings remain. Optimizing informal communication and ensuring equal participation are recommended to improve organizational effectiveness.